The Impact of FDI and R&D Input on China's Energy Intensity - Based on Empirical Study of Provinces Along the Belt and Road - Zhang, Xinyu (International Journal of Global Economics and Management, 2024)
Since the Belt and Road Initiative was proposed and implemented in 2013, China's economic scale and growth rate rank among the top in the world, and foreign-invested enterprises have become an important engine to promote China's high-quality economic development. How to effectively utilize foreign investment to reduce China's energy intensity is crucial to sustainable and stable economic development. Based on the panel data of 17 provinces along the "Belt and Road" in China from 2011 to 2020, this paper established a fixed-effect model to investigate the influence of foreign investment utilization level on energy intensity. The results show that foreign direct investment, regional economic development level and research and development intensity have a significant effect on the decline of energy intensity. Factors such as industrial structure and energy structure will cause the increase of energy intensity. The results of subregional regression show that FDI inflow helps to reduce the energy intensity of the eastern and central regions, and the effect of the eastern region is better than that of the central region, but the energy intensity of the western region will increase. Based on the above, suggestions are put forward to rationally guide the inflow of foreign capital in different regions, increase the research and development of energy-saving technologies, accelerate the transformation and upgrading of industrial structure, and optimize the structure of energy consumption, in order to improve the utilization rate of energy in our country.